ANALYSIS OF IGRP PERFORMANCE IN WDS MESH TOPOLOGY BASED ON IEEE 802.11 STANDARDS - Arief ikhwan Wicaksono; Chanief Budi Setiawan (Compiler, 2018)
Redundancy and robustness are the most common problems in a wireless network distribution system, network system problems that are not able to handle coverage areas in a large / wide coverage, so that the network users are easily disconnected from the connection and out of the server radius. These problems are caused by topology and wireless network distribution methods that are not in accordance with the needs and coverage of its users. However, adding a number of access points en masse to expand the network without being based on appropriate applied methods, is not necessarily able to minimize complaints from network users. Starting from the problems described in the previous paragraph, in this study a wireless distribution mesh system topology (WDS mesh) will be built to improve utility and network usage in the area / radius of the area between access points using wireless lines and minimize cable requirements which are generally the main constraints in network deployment and installation to areas that are difficult to reach. The topology built in this research will implement the wireless routing protocol that results from the analysis and observation process to expand the expansion of service areas to places that are difficult to reach. The wireless routing protocol method used in this study is the Made Mesh Easy (MME) method which is one of the developments of the Interior Gateway Routing Protocol (IGRP) method. Evaluation of the wireless routing protocol in the WDS mesh network topology will be carried out periodically to obtain the results of the analysis that will be used to re-configuring and re-routing to maintain the quality of the network remains realiable. Mesh clients will give feedback on the quality of service obtained based on observations according to IEEE 802.11 standardization. The parameters used are: Througput, Packet Loss Ratio, Latency, Jitter, MOS, Post Dial Delay and Echo Cancelation (EC)